Мікроструктура та механічні властивості шаруватого литого композиту ВТ-6/Al - Смірнова, Яна; Гурія, Ірина (Physico-technological Institute of Metals and Alloys, 2023)
Layered titanium/aluminum composite materials based on pure metals and their alloys are widely investigated due to their unique properties. However, the most common solid-phase methods have some disadvantages that can be avoided by using simplified liquid-phase casting technologies. In the presented work the interface microstructure and mechanical behavior during tensile test of the VT-6/Al composite produced using the liquid-phase casting method are investigated. The technology of manufacturing VT-6/Al layered material consisted in infiltration of several titanium plates’ package with molten aluminum. It was found that aluminum evenly infiltrates between the plates and 3.03–4.33 μm thick transition layer is formed at the interface. It consists of a solid solution of titanium in aluminum and single grains of Al3Ti and AlTi phases. The number of infiltrated titanium plates and the gap changing between them does not affect at the thickness of the formed transition layer. It was found that the main parameter that affects the mechanical properties is the ratio of the thicknesses of the Ti to Al layers. The rule of mixture is analyzed and the tensile strength for five- and seven-layer materials is determined. Despite the fact that the values of tensile strength of the obtained composites are reduced compared to the original titanium grade VT-6, layered materials due to their structure can improve fracture resistance and positively effect on damping mechanisms. Therefore, further study of the layered titanium/aluminum composite materials behavior under perpendicular load to their layers is relevant.